Scoring Mental Health Quality of Life With the SF-36 in Patients With and Without Diabetes Foot Complications. (March 2018) - Ahn, Junho; Del Core, Michael A.; Wukich, Dane K.; Liu, George T.; Lalli, Trapper; VanPelt, Michael D.; La Fontaine, Javier; Lavery, Lawrence A.; Raspovic, Katherine M.
The aim of this study was to examine if using orthogonal and oblique factor analysis detect changes in health-related quality of life differently in diabetic patients on the Short Form-36 (SF-36) survey. A total of 155 patients had diabetic foot complications (DFC), and 145 patients had no DFCs. The SF-36 Physical Component Summary (PCS) and Mental Component Summary (MCS) scores were calculated using scoring coefficients determined by orthogonal and oblique rotation principle component analyses of the subscales. The DFC group had lower orthogonal ( P < .00001) and oblique PCS scores ( P < .00001). However, despite lower Mental Health subscale scores in the patients with DFCs, orthogonal MCS scores ( P = .156) did not differ. In contrast, the oblique MCS scores reflected the difference in the Mental Health subscale ( P = .0005). Orthogonal and oblique PCS scores did not differ significantly. However, orthogonal MCS scores were significantly higher than oblique MCS scores in those with DFCs ( P = .0004) and without DFCs ( P = .005). The shorter, 12-item SF-12 survey demonstrated similar results. Poorer physical function leads to higher orthogonal MCS scores than if determined by oblique scoring coefficients since Physical Function, Bodily Pain, and General Health are weighted more negatively in orthogonal coefficients when calculating the MCS score. Oblique scoring coefficients may address this issue, but further study is necessary to confirm whether oblique MCS scores accurately represent the mental health of patients with diabetic foot disease.